Metabolic syndrome extenuation in rat model by feeding Stevia rebaudiana Bertoni cookies - Muhammad Farhan Jahangeer Chughtai; Imran Pasha; Samreen Ahsan; Tariq Mehmood; Muhammad Zubair Khalid; Muhammad Adil Farooq; Atif Liaqat; Adnan Khaliq; Saira Tanweer; Mădălina Ungureanu-Iuga; Ionica Cotovanu; Abdullah Ali Alkahtane; et al. (Cogent Food & Agriculture)
Stevia rebaudiana is zero-calorie bio-sweetener and furnishes the best nutrition out of it. The study was conducted to characterize the extracts from water, ethanol, methanol, and supercritical fluid for Steviosides/SGs. The compounds found in appreciable quantities were Stevioside (665.34 ± 27.27 to 1107.95 ± 50.96 mg/kg), Rebaudioside A (383.38 ± 17.25 to 792.15 ± 38.02 mg/kg) and Steviol (357.26 ± 14.64 to 485.25 ± 22.32 mg/kg). Stevia cookies were prepared by replacing sucrose with Stevia powder (10%), water extract (1%), and supercritical extract (3%). Bio-efficacy rats modeling trials were done to check their impact against hyperglycemia and hypercholesterolemia. Blood glucose level was reduced from 4.54 to 7.00%, insulin level was increased by 4.27 to 6.13% due to diets enriched with stevia powder and extracts as compared to the control. In hypercholesterolemic rats, up surged cholesterol level was reported to reduce as a function of Stevia powder and extracts from 1.28 to 5.47%. Substantial increment in HDL, and reduction in LDL and triglycerides was recorded in Stevia leaves powder and extracts treatments by 2.79–6.66%, 2.68–4.16%, and 3.12–5.36, respectively. Stevia cookies administration in rats showed non-significant impact on the liver, renal, and hepatological parameters, while the safety of cookies was improved. Therefore, it can be concluded from the outcomes that in addition to sweetness, Stevia health health-beneficial effects make it suitable to be included in cookies.